Fatigue Properties of Steel with Increased Atmospheric Corrosion Resistance - Bursak, Marian; Bokuvka, Otakar (Communications - Scientific Letters of the University of Zilina, 2009)
The paper deals with the influence of cyclic loading (tension-compression, bending and torsion) on the course of the fatigue life and the fatigue limit of advanced low-alloyed strip steel with increased atmospheric corrosion resistance. The tested steel shows, besides very good mechanical properties (Re 380 MPa, A5 30%), also very good fatigue resistance and its fatigue limit/ultimate tensile strength ratio is above 0.5. These properties are provided by a favourable fine-grained structure of the tested steel.
Keywords: no keywords